Efficiency of a braking process evaluating the roughness of road surface - Bogdevičius, Marijonas; Vladimirov, Oleg (Transport, 2006)
Transport traffic safety depends on many factors; one of them being the efficiency of the vehicle braking. The efficiency of the vehicle depends on the reaction of the driver, the braking system, the quality of tires, the characteristics of the road surface. The vehicle with the hydraulic braking system and a disc brake with the wheel has been investigated. The dynamic models of the disk brake assembly and the wheel have been constructed. The braking distances of the vehicle with a hydraulic ABS on the asphalt concrete pavement with shortwave roughness and different initial velocity are obtained.First Published Online: 27 Oct 2010